Remarks from the G20 Finance Ministers Conference Call on COVID-19 - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, World Bank Group President, issued his remarks from the G20 Finance Ministers conference call, on the COVID-19 pandemic. These are difficult times for all, especially for the poorest and most vulnerable. For the World Bank Group, the first goal is to provide prompt support during the crisis, based on a country’s needs. It is also vital to shorten the time to recovery and create confidence that the recovery can be strong. On March 17, the World Bank and IFC Boards approved a USD14 billion package to respond to COVID-19. Of that, IFC is making USD8 billion available in relatively fast-acting financial support for private companies. IBRD and IDA will be making USD6 billion available in the near term to support health care. The Bank is currently restructuring existing projects in 23 countries, many of these through the use of contingent emergency response components. The Bank is also preparing projects in 49 countries in a new fast-track facility, with decisions expected this week on as many as 16 country programs. The World Bank’s Board will meet shortly, and it is expected that this first round of countries will provide a framework to quickly scale up over the next few weeks. The Bank and the IMF are ready to work quickly with official bilateral creditors and with other international organizations as partners to finalize a process by the Spring Meetings of our organizations in April.